2015
DOI: 10.1155/2015/343682
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Patterns of c-Fos and c-Jun Induced by Different Frequencies of Electroacupuncture in the Brain

Abstract: To investigate patterns of c-Fos and c-Jun expression induced by different frequencies of electroacupuncture (EA) in the brain, goats were stimulated by EA of 0, 2, 60, or 100 Hz at a set of “Baihui, Santai, Ergen, and Sanyangluo” points for 30 min. The pain threshold was measured using the potassium iontophoresis method. The levels of c-Fos and c-Jun were determined with Streptavidin-Biotin Complex immunohistochemistry. The results showed that the pain threshold induced by 60 Hz was 82.2% higher (P < 0.01) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 49 publications
(60 reference statements)
1
24
0
1
Order By: Relevance
“…Acupoint is another important factor influencing EAA. Studies have demonstrated that EA stimulation at a set of Baihui and Santai acupoints can elicit an effective analgesia in goats [ 28 , 31 33 ]. Zusanli acupoint has been widely used to induce analgesic effect in rats [ 8 ], rabbits [ 40 ], and humans [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acupoint is another important factor influencing EAA. Studies have demonstrated that EA stimulation at a set of Baihui and Santai acupoints can elicit an effective analgesia in goats [ 28 , 31 33 ]. Zusanli acupoint has been widely used to induce analgesic effect in rats [ 8 ], rabbits [ 40 ], and humans [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here the acupoints are nominated with Pinyin Naming System instead of the Meridian Numbering System because animal's meridians are not completely recorded. The anatomical locations of these acupoints have been described in detail for use in veterinary medicine [ 28 , 31 33 ]. The Baihui acupoint was identified on the dorsal midline between the spinous processes of the last lumbar and the first sacral vertebrae.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our included studies, most of low-frequency stimulated EA decreased the activity of the LC whereas high frequency increased the activity of the LC, except in the studies of Kwon et al [ 26 ], Lee and Beitz [ 25 ], and Qiu et al [ 28 ]. In the studies of Kwon et al and Lee and Beitz, the low frequency (4 Hz) of EA increased the c-Fos expression in the LC.…”
Section: Discussionmentioning
confidence: 99%
“…Qiu et al [ 28 ] used two-year-old healthy hybrid male goats to evaluate the levels of c-Fos and c-Jun expression induced by EA in the brain. EA were administered at a set of GV20, Santai, Ergen (AH1), and Sanyangluo (TE8), and four different frequencies, such as 0, 2, 60, and 100 Hz, were used.…”
Section: Modulation Of Lc Neuronal Cells By Acupuncturementioning
confidence: 99%